2022
DOI: 10.3233/shti220450
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cut Off for Endometrial Thickness in Couples with Unexplained Infertility: Trustable AI

Abstract: Endometrial thickness in assisted reproductive techniques is one of the essential factors in the success of pregnancy. Despite extensive studies on endometrial thickness prediction, research is still needed. We aimed to analyze the impact of endometrial thickness on the ongoing pregnancy rate in couples with unexplained infertility. A total of 729 couples with unexplained infertility were included in this study. A random forest model (RFM) and logistic regression (LRM) were used to predict pregnancy. Evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mehrjerd et al aimed to analyze the impact of endometrial thickness on the ongoing pregnancy rate in couples with unexplained infertility using deep machine learning & artificial intelligence based algorithms [13]. They obtained a 7.7 mm cut-off point for IUI and 9.99 mm for IVF/ICSI treatment.…”
Section: Implantation Prediction Algorithms Studying the Endometriummentioning
confidence: 99%
“…Mehrjerd et al aimed to analyze the impact of endometrial thickness on the ongoing pregnancy rate in couples with unexplained infertility using deep machine learning & artificial intelligence based algorithms [13]. They obtained a 7.7 mm cut-off point for IUI and 9.99 mm for IVF/ICSI treatment.…”
Section: Implantation Prediction Algorithms Studying the Endometriummentioning
confidence: 99%
“…Despite extensive studies on endometrial thickness prediction, research is still needed. Mehrjerd et al aimed to analyze the impact of endometrial thickness on the ongoing pregnancy rate in couples with unexplained infertility using deep machine learning & artificial intelligence based algorithms 36 . A total of 729 couples with unexplained infertility were included in this study.…”
Section: Deep Machine Learning Aided Implantation Prediction Algorith...mentioning
confidence: 99%
“…In a randomized controlled study conducted by Quaas et al, although it was thought that increased endometrial thickness was associated with high live birth rates, it was reported that there were significant live pregnancy rates even in thin endometrium and that the cycle should not be canceled due to thin endometrium (18). Nonetheless, another studystated that endometrial thickness was important for achieving viable pregnancy, and in patients with unexplained infertility, the optimal thickness for IUI treatment was considered to be 7.7 mm (19). A meta-analysis that was conducted revealed that there was no connection between endometrial thickness and pregnancy rates in IUI cycles (20).…”
Section: Characteristicmentioning
confidence: 99%